2017
DOI: 10.1002/ird.2125
|View full text |Cite
|
Sign up to set email alerts
|

Improving Modelling of Discharge Coefficient of Triangular Labyrinth Lateral Weirs Using SVM, GMDH and MARS Techniques

Abstract: In this study the discharge coefficient (Cd) of labyrinth lateral weirs was modelled and predicted using artificial neural network (ANN), adaptive neuro fuzzy inference system (ANFIS), support vector machine (SVM), group method of data handling (GMDH), and multivariate adaptive regression splines (MARS) techniques. To this end, a related data set was collected from the literature. Results indicated that the proposed ANN model includes two hidden layers with eight and five neurons in the first and second hidden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 55 publications
(47 reference statements)
0
9
0
1
Order By: Relevance
“…GMDHNN is successfully applied in diverse engineering applications [31][32][33][34]. Within hydrology and water resources related research, Najafzadeh et al [35] developed the GMDHNN model for scour depth (SD) of pipelines estimation due to waves variability; the prediction of local SD at bridge abutments in coarse sediments with thinly armored beds was conducted by Najafzadeh et al [36]; simulation of flow discharge of straight compound channels was reported by Najafzadeh and Zahiri [37]; prediction of significant wave height was established by Shahabi et al [38]; prediction of turbidity considering daily rainfall and discharge data was determined by Tsai and Yen [39]; an improved modeling of the discharge coefficient for triangular labyrinth lateral weirs was described by Parsaie and Haghiabi [40]; an evaluation of treated water quality in a water treatment plant was carried out by Alitaleshi and Daghbandan [41]; a prediction of turbidity and the free residual aluminum of drinking water was tested by Daghbandan et al [42]. Based on the reported literature review, only one study reported the implementation of the GMDHNN ET 0 modeling developed by da Silva Carvalho and Delgado [43].…”
Section: Introductionmentioning
confidence: 99%
“…GMDHNN is successfully applied in diverse engineering applications [31][32][33][34]. Within hydrology and water resources related research, Najafzadeh et al [35] developed the GMDHNN model for scour depth (SD) of pipelines estimation due to waves variability; the prediction of local SD at bridge abutments in coarse sediments with thinly armored beds was conducted by Najafzadeh et al [36]; simulation of flow discharge of straight compound channels was reported by Najafzadeh and Zahiri [37]; prediction of significant wave height was established by Shahabi et al [38]; prediction of turbidity considering daily rainfall and discharge data was determined by Tsai and Yen [39]; an improved modeling of the discharge coefficient for triangular labyrinth lateral weirs was described by Parsaie and Haghiabi [40]; an evaluation of treated water quality in a water treatment plant was carried out by Alitaleshi and Daghbandan [41]; a prediction of turbidity and the free residual aluminum of drinking water was tested by Daghbandan et al [42]. Based on the reported literature review, only one study reported the implementation of the GMDHNN ET 0 modeling developed by da Silva Carvalho and Delgado [43].…”
Section: Introductionmentioning
confidence: 99%
“…+ and − are Lagrange values determined by + and − . Verities of kernel functions are introduced in SVR; nonetheless, linear, polynomial, RBF, and Sigmoid kernel functions are more prevalent in solving general problems [21], [22]. Among the mentioned kernel functions, RBF, due to its higher efficiency, is more accomplished in complex problems [18], [34]; thus, the present study employs the RBF kernel function in SVR.…”
Section: Support Vector Regression (Svr)mentioning
confidence: 99%
“…Parsaie and Haghiabi [21], through comparison of three popular ANNs (i.e., Multi-Layer Perceptron (MLP), SVR and RBFNN), found that in a triangular LW, SVR predicts C d more accurate than MLP and RBFNN. Nevertheless, in another study on triangular LW, which was conducted by the same scholars [22], MLP not only performed better than SVR but also was superior to ANFIS, Group Method of Data Handling (GMDH), and Multivariate Adaptive Regression Splines (MARS). Likewise, Norouzi et al [8] reported the superiority of MLP over SVR and RBFNN in estimating C d in a trapezoidal LW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various researchers have been used various data mining and data-driven techniques in civil and environmental engineering applications (Mehdipour, Stevenson, Memarianfard, & Sihag, 2018;Nain, Sihag, & Parsaie, 2016;Parsaie, Azamathulla, & Haghiabi, 2018;Parsaie & Haghiabi, 2017, 2015Parsaie, Najafian, Omid, & Yonesi, 2017;Sihag, 2018;Sihag, Singh, Vand, & Mehdipour, 2018a;Sihag, Tiwari, & Ranjan, 2018bSingh, Sihag, & Singh, 2017;Singh, Sihag, Singh, & Kumar, 2018;Tiwari, Sihag, Kumar, & Ranjan, 2018;Vand, Sihag, Singh, & Zand, 2018). Asadollahfardi, Hemati, Moradinejad, and Asadollahfardi (2013) used ANN to predict the SAR in which Na, Mg, Ca, SO 4 , Cl, HCO − 3 , pH were input variables and SAR was output and found that ANN has the capability to predict the SAR accurately and precisely.…”
Section: Introductionmentioning
confidence: 99%